Pain relief in a young woman with adhesive capsulitis after manual manipulation of the acromioclavicular joint for remaining symptoms after mobilisation under anaesthesia. (9th November 2014) - Lilje, Stina; Genberg, Madeleine; Aldudjaili, Hassan; Skillgate, Eva
Abstract : Adhesive capsulitis is a painful condition with a prevalence of 2–5%. There is a lack of evidence for its aetiology and for conventional treatment and cost effects. This study describes the treatment effects of manual manipulation of the acromioclavicular joint for adhesive capsulitis in a young woman for persisting pain after mobilisation of the glenohumeral joint under anaesthesia. Primary outcomes were pain and physical function, measured by a visual analogue scale and the SF36 health survey. Secondary outcomes were sleep pattern, medication and perceived recovery. The mobility after manipulation under anaesthesia: elevation 55° and no improvement in pain. After manual manipulation: unrestricted elevation and significant pain relief. The patient no longer suffered from sleeping disorders and ceased all medication. Considering the lack of knowledge in aetiology and treatment, specialised manual examination of the acromioclavicular joint should be considered early in patients diagnosed with adhesive capsulitis.